Interdigitating dendritic cell sarcoma of the liver and lung: a case report with morphohological and immunohistochemical features of tumor - Svjetlana Radović; Mirsad Dorić; Hamza Žujo; Ajna Hukić; Suada Kuskunović; Mirsad Babić; Ivana Tomić (Biomolecules & Biomedicine, 2012)
Interdigitating dendritic cell sarcoma is extremely rare neoplasm that mainly occurs in the lymph nodes. Only 45 cases have been reported in the literature to date.